2022
DOI: 10.1159/000526354
|View full text |Cite
|
Sign up to set email alerts
|

Serum Prealbumin Levels on Admission as a Prognostic Marker in Stroke Patients Treated with Mechanical Thrombectomy

Abstract: Background: Prealbumin is a marker of malnutrition and inflammation. It has been associated with poor prognosis in cardiovascular disease, but less is known in stroke patients. Our objective was to evaluate the association of prealbumin levels at admission with prognosis in patients with stroke treated with mechanical thrombectomy. Material & Methods: Retrospective study of a prospective database of consecutive patients treated with mechanical thrombectomy. Clinical, radiological and blood parameters inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Similarly, a lower transthyretin concentration at admission in stroke patients is an independent predictor of long-term mortality after mechanical thrombectomy [21] . Additionally, acute heart failure patients with transthyretin concentration ≤ 15mg/dL at discharge have higher 6-month morbidity and mortality [14] .…”
Section: Discussionmentioning
confidence: 98%
“…Similarly, a lower transthyretin concentration at admission in stroke patients is an independent predictor of long-term mortality after mechanical thrombectomy [21] . Additionally, acute heart failure patients with transthyretin concentration ≤ 15mg/dL at discharge have higher 6-month morbidity and mortality [14] .…”
Section: Discussionmentioning
confidence: 98%
“…Prealbumin is a marker of malnutrition and inflammation. It has been associated with poor prognosis in cardiovascular disease ( López et al., 2022 ), but less is known in HBV-ACLF patients. This study found that lower prealbumin levels after ALSS treatment are independently associated with in-hospital mortality.…”
Section: Discussionmentioning
confidence: 99%